132k views
2 votes
Solve for X.
2x/3 + 1 =3

2 Answers

3 votes

Answer:

x=3

Step-by-step explanation:

Combine 2 and x/3.

2x/3+1=3

Move all terms not containing x to the right side of the equation.

2x/3=2

Multiply both sides of the equation by 3/2.

3/2⋅2x/3=3/2⋅2

Simplify both sides of the equation.

x=3

User XMythicx
by
6.6k points
5 votes

Step-by-step explanation:


(2x)/(3) + 1 = 3 \\ \\ (2x + 3)/(3) = 3 \\ \\ 2x + 3 = 9 \\ 2x = 9 - 3 \\ 2x = 6 \\ \\ x = (6)/(2) \\ \\ x = 3

User Asjer
by
6.9k points